An Adaptive Finite Element Method for Initial-Boundary Value Problems for Partial Differential Equations - Davis, Stephen F; Flaherty, Joseph E (SIAM journal on scientific computing, 1982)
A finite element method is developed to solve initial-boundary value problems for vector systems of partial differential equations in one space dimension and time. The method utomatically adapts the computational mesh as the solution progresses in time and is, thus, able to follow and resolve relatively sharp transitions such as mild boundary layers, shock layers or wave fronts. This permits an accurate solution to be calculated with fewer mesh points than would be necessary with a uniform mesh. The overall method contains two parts, a solution algorithm and a mesh selection algorithm. The solution algorithm is a finite element-Galerkin method on trapezoidal space-time elements, using either piecewise linear or cubic polynomial approximations, and the mesh selection algorithm builds upon similar work for variable knot spline interpolation. A computer code implementing these algorithms has been written and applied to a number of problems. These computations confirm that the theoretical error estimates are attained and demonstrate the utility of variable mesh methods for partial differential equations.